Explanation on types of scientific articles for publication in the Revista de Ciências Agroveterinárias - Carvalho, Leonardo Bianco de (Revista de Ciências Agroveterinárias, 2018)
As a result of several questions and difficulties of some authors in understanding the difference between complete article and scientific note, as well as what is a review article, the objective of this editorial note is to clarify to editors, authors and readers of the Revista de Ciências Agroveterinárias a the types of articles that are published in this journal. It is also included that this journal will standardize the types of articles, from 2018, as Research Article (full article), Research Note (scientific note) and Review Article (literature review). In addition, this journal publishes communications of the publishers as Nota Editorial. The three types of articles published by the journal, Research Article, Research Note and Review Article, are scientific articles derived from research conducted by the authors. Research articles and research notes are usually derived from original experimental research and, therefore, based on results obtained experimentally by the authors. Review articles are derived from non-experimental research, that is, not based on results obtained experimentally, but rather based on the knowledge (results and conclusions) generated so far on a given subject. Research article and research note are therefore similar according to their empirical basis. However, there are differences between these two types of articles that go beyond the extension of the text. Research notes are short, short texts with small results, but that generate unprecedented conclusion (s) as a result of a new fact discovered by the authors. In this way, its publication is justified due to the importance of the discovery, that is, of the scientific knowledge generated, even though there is not a large volume of results. Research articles are, in turn, longer texts, with greater volume of results, which also generate unprecedented conclusions as a result of new scientific discoveries. Therefore, it should be clear that research articles and research notes are equally important in the construction of scientific knowledge. Thus, an article with a small volume of results, in which the authors increase the information of the introduction and the discussion, in order to increase the number of pages, will not, in essence, be a complete article (Research Paper). Nor will a full article whose text is "lean" be characterized as a scientific note (Research Note), because its essence is not the same. So while overall articles are generally longer than scientific notes, it is not the number of pages that defines what is one and what is another. Review article, in turn, is not limited to the presentation (or meeting) of the scientific knowledge generated so far in a single article. Structurally, review articles are similar to full papers or scientific notes, presenting the justification, the objective, the methodology, the results (referring to the knowledge generated so far), the discussion (which is the author’s critical view on the generated knowledge) and the conclusion (which is the unpublished scientific knowledge generated by the author, based on the scientific knowledge we had so far). Therefore, a review article should generate new scientific knowledge, not just gather information (knowledge) already present in the literature. Another type of scientific paper explored most recently is the meta-analysis. Meta-analysis is a synthesis of previous research on a (often polemical) subject, which emphasizes the production of quantitative conclusions, aiming at extracting additional information from pre-existing data through the union of the results of several works and the application of a or more statistical techniques (UFSM 2017). Meta-analysis is not derived from an original research, but from the analysis of previously published research, and therefore is included as Review Article. It is hoped, in conclusion, that the doubts regarding the articles published by the Revista de Ciências Agroveterinárias have been remedied and that this brief note will help the writing of future works to be submitted and published in this journal.